Improved heuristics for multicast routing in wireless mesh networks - Matam, Rakesh; Tripathy, Somanath (Wireless networks, 2013)
Multicast is a communication technique that allows a source to transmit data to a set of recipients in an efficient manner. Therefore, the primary objective of a multicast routing protocol would be to minimize number of transmissions to conserve bandwidth. The problem of computing multicast trees with minimal bandwidth consumption is similar to Steiner tree problem and has shown to be NP-complete. So, heuristic based algorithms are suitable to approximate such bandwidth optimal trees. This paper proposes a multicast routing protocol based on minimum number of transmission trees using an heuristic approach. The simulation results show that the proposed algorithm offers better performance over existing protocols, even in the worst-case scenario when the set of multicast receivers are sparsely distributed across the network.